The hidden power of Photoshop Elements 3 - Lynch, Richard (SYBEX, 2005)
In this thorough update of his award-winning best-seller, Richard Lynch supplies those tools, plus the in-depth background and detailed instruction you need to apply them effectively. In no time, you'll be using Photoshop Elements to get results you never thought possible.